Interphace energy of aluminum crystals at the boundary with nonpolar organic liquids - A.M. Apekov; I.G. Shebzukhova; L.A. Khamukova (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов)
Understanding the energy characteristics at the metal-organic interface is of great importance for the development of equipment and technologies in various industries. In this regard, there is a great interest in studying the processes occurring at this interface. Particularly noteworthy is the rapid growth of studies on the properties of metal-organic framework structures, which is associated with the possibility of synthesizing these structures with the desired properties by varying the lengths of the organic molecules connecting the atoms of metals or their oxides, as well as by selecting the chemical composition. In this paper, the values of the interfacial energy at the boundaries of the faces of an aluminum crystal with organic liquids are obtained within the framework of the electron-statistical method, taking into account the polarization of metal ions and molecules of the organic liquid, as well as the dispersion interaction of Wigner-Seitz cells on the interface. The dependence of the interfacial energy and corrections to the interfacial energy on the permittivity of the liquid and the orientation of the metal crystal is obtained. It is found that the dispersion correction makes a positive contribution while the polarization correction reduces the interfacial energy.